2018
DOI: 10.1017/jfm.2018.454
|View full text |Cite
|
Sign up to set email alerts
|

Energy flux enhancement, intermittency and turbulence via Fourier triad phase dynamics in the 1-D Burgers equation

Abstract: We present a theoretical and numerical study of Fourier space triad phase dynamics in one-dimensional stochastically forced Burgers equation at Reynolds number Re ≈ 2.7 × 10 4 . We demonstrate that Fourier triad phases over the inertial range display a collective behaviour characterised by intermittent periods of synchronisation and alignment, reminiscent of Kuramoto model (Kuramoto 1984) and directly related to collisions of shocks in physical space. These periods of synchronisation favour efficient energy fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…At smaller scales, the effects of rotation would be negligible and strongly nonlinear dynamics would dominate. Given that the shallow water equations are similar to the compressible gas dynamics equations (Whitham 2011), shocks in RSW models at small scales may be expected to generate a wave spectrum close to at these small scales, as is the scenario in compressible flows (Kuznetsov 2004; Falkovich & Kritsuk 2017; Gupta & Scalo 2018; Murray & Bustamante 2018).…”
Section: The Modelmentioning
confidence: 99%
“…At smaller scales, the effects of rotation would be negligible and strongly nonlinear dynamics would dominate. Given that the shallow water equations are similar to the compressible gas dynamics equations (Whitham 2011), shocks in RSW models at small scales may be expected to generate a wave spectrum close to at these small scales, as is the scenario in compressible flows (Kuznetsov 2004; Falkovich & Kritsuk 2017; Gupta & Scalo 2018; Murray & Bustamante 2018).…”
Section: The Modelmentioning
confidence: 99%
“…In particular, a triad phase, φ 1 ( p) + φ 1 ( q) − φ 1 ( k), is explicitly represented on the right-hand side, indicating the link between S k and the phase of velocities (see Refs. [11,[38][39][40] for more discussions). This expression explicitly illustrates that both the amplitudes and the phases can affect the evolution of S k .…”
Section: Discussionmentioning
confidence: 99%
“…While Gaussian random fields feature completely uncorrelated phases, phase correlations can give rise to complex scale-dependent statistics, and it is well known that coherent spatial structures such as shocks require a high level of correlation amongst the phases of the Fourier modes. Notably, so far only very few studies have addressed the connection between the emergence of coherent intermittent structures in real space, non-Gaussian statistics and phase correlations, indicating that bursts of spectral energy fluxes (and dissipation) are produced when Fourier phases become correlated [9][10][11]. Elucidating these connections is important for both fundamental and applied aspects.…”
mentioning
confidence: 99%
“…This infinite set of coupled ODEs describes the full Burgers dynamics of the Fourier phases and amplitudes. Recently, it was shown that the dynamics of the Fourier phases φ k (t) determine to a great extent the shock dynamics and the associated non-Gaussian statistics [9,11]. Thus, we take equation ( 3) as a starting point for a minimal model for Fourier phase dynamics in turbulence, the "phase-only" model.…”
mentioning
confidence: 99%
See 1 more Smart Citation